Художній наратив Агатангела Кримського-філолога - Єрмоленко, С. (Культура слова, 2021)
У статті запропоновано лінгвософський підхід до художньої мовотворчості А. Кримського, історика-сходознавця, письменника (прозаїка і поета), поліглота, філолога, перекладача. Минуло понад сто років, як А. Кримський написав роман «Андрій Лаговський», а художній наратив автора викликає інтерес не лише істориків української літератури, а й культурологів, психологів, істориків мови. Аналіз художнього наративу Кримського-філолога здійснено в таких аспектах: мовно-структурна характеристика тексту (лексика, фразеологія, синтаксис) у порівнянні з літературною нормою сучасної української мови, прагмалінгвістичне моделювання маркерів тодішнього суспільства, репрезентованих мовними портретами персонажів, реагування автора-філолога на мову спілкування персонажів. Зроблено висновок про взаємодію розмовних і книжних (іншомовні запозичення) джерел у сучасній рецепції історії української літературної мови кінця ХІХ – початку ХХ ст. The article offers a linguosophical approach to the artistic linguistics of A. Krymskyi, historian-orientalist, writer (prose writer and poet), polyglot, philologist, translator. More than a hundred years have passed since A. Krymskyi wrote the novel “Andriy Lahovskyi”, and the author’s artistic narrative is of interest not only to historians of Ukrainian literature, but also to culturologists, psychologists, and language historians. The analysis of the artistic narrative of the Krymskyi as philologist is carried out in the following aspects: linguistic and structural characteristics of the text (vocabulary, phraseology, syntax) in comparison with the literary norm of modern Ukrainian, pragmalinguistic modeling of markers of the society represented by linguistic portraits of characters. characters. The conclusion about the interaction of colloquial and book (foreign language borrowings) sources in the modern reception of the history of the Ukrainian literary language of the end of the XIX - the beginning of the XX century is made. Numerous foreign words-terms, in particular in the field of psychiatry, are indicative of A. Krymskyi’s artistic narrative, especially when it comes to the state of the character’s psyche. foreign terminological vocabulary contrasts with the emotionally expressive content of colloquial structures, Ukrainian phraseology and interspersed foreign language mintexts. Text markers of social stratification of society include psycholinguistic evaluative statements of the author about the situational behavior of the characters. A. Krymskyi’s artistic narrative reveals signs of the author’s philological thinking, his constant attention to the explanation of the meanings of words, to the translation of foreign names. A significant number of lexical, word-forming, grammatical variants of the Ukrainian language are recorded in the individual style of the writer. Comparing them with lexicographic sources reveals the author’s preferences, time markers of the dynamic literary norm of the late nineteenth - early twentieth century.